Work quality assessment of a cherry sorting machine - Ancza, E.; Csizmazia, Z.; Polyák, N. I.; Farkas, E.; Nyéki, J.; Szabó, Z. (International Journal of Horticultural Science, 2011)
The conditions of the cultivation of marketable cherries are diverse. Choosing the production site on the basis of the climatic conditions, selecting the most appropriate variety taking into account the region and the purpose of the production, utilization of the optimal production method, to ensure the required water and nutrients supply, frost and hail protection techniques, modern technology in crop protection, and professional performance of harvesting and handling, to name just a few of the most important issues. The objective of present study is to determine the qualitative characteristics of the UNITEC cherry sorting machine.